The Effect of Urbanization on the Physiology and Behaviour of Common Garter Snakes (Thamnophis sirtalis) - Agnew, Stephanie (Université d'Ottawa / University of Ottawa, 2026)
The world is in a major biodiversity crisis, mainly driven by anthropogenic land use, including urbanization. To predict future population changes, conservationists often require high resolution, long-term data on changes in abundance. The predictive timeline framework of population collapse suggests that individual metrics of condition, such as behaviour and physiology, change in a predictable pattern before abundance declines, which would provide conservationists with more time to enact remediation measures. My objective was to determine how urbanization affects the behaviour and physiology of common garter snakes (Thamnophis sirtalis), and whether these changes are in line with the predictive timeline framework. I captured 220 snakes from 35 old fields in Ottawa/Gatineau, Canada, from April to October 2025; I chose the sites to vary in the amount of urbanization in the surrounding landscape. I recorded the snakes' antipredator behaviour and took a blood sample. There was no difference in snake abundance across the urbanization gradient. Snakes in areas surrounded by more urbanization used fewer antipredator behaviours, were less likely to be infected with hemoparasites, and those who were infected had lower parasite loads. The likelihood to flee before capture, body condition, heterophil to lymphocyte ratio, and plasma free glycerol did not differ across the urbanization gradient. My results provide some support for a predictable sequence of changes in individuals, in which behaviour is altered before physiology, and both are affected before declines in abundance are apparent. This framework must be tested in the field further to determine its applicability across different taxa and environmental stressors.
Keywords: Ecology; Conservation; Reptile; Hematology; Antipredator behaviour; Parasites